Boost your presentation IQ - Pincus, Marilyn (McGraw-Hill, 2006)
Boost Your Presentation IQ reveals how you can create powerful presentations and speeches for any business setting. Through an interactive format that features multiple-choice questions, you will determine your "Presentation IQ."